Effects of ergonomic intervention on work-related upper extremity musculoskeletal disorders among computer workers: a randomized controlled trial - Esmaeilzadeh, Sina; Ozcan, Emel; Capan, Nalan (International archives of occupational and environmental health, 2014)
Purpose The aim of the study was to determine effects of ergonomic intervention on work-related upper extremity musculoskeletal disorders (WUEMSDs) among computer workers. Methods Four hundred computer workers answered a questionnaire on work-related upper extremity musculoskeletal symptoms (WUEMSS). Ninety-four subjects with WUEMSS using computers at least 3 h a day participated in a prospective, randomized controlled 6-month intervention. Body posture and workstation layouts were assessed by the Ergonomic Questionnaire . We used the Visual Analogue Scale to assess the intensity of WUEMSS. The Upper Extremity Function Scale was used to evaluate functional limitations at the neck and upper extremities. Health-related quality of life was assessed with the Short Form - 36 . After baseline assessment, those in the intervention group participated in a multicomponent ergonomic intervention program including a comprehensive ergonomic training consisting of two interactive sessions, an ergonomic training brochure, and workplace visits with workstation adjustments. Follow-up assessment was conducted after 6 months. Results In the intervention group, body posture ( p < 0.001) and workstation layout ( p = 0.002) improved over 6 months; furthermore, intensity ( p < 0.001), duration ( p < 0.001), and frequency ( p = 0.009) of WUEMSS decreased significantly in the intervention group compared with the control group. Additionally, the functional status ( p = 0.001), and physical ( p < 0.001), and mental ( p = 0.035) health-related quality of life improved significantly compared with the controls. There was no improvement of work day loss due to WUEMSS ( p > 0.05). Conclusions Ergonomic intervention programs may be effective in reducing ergonomic risk factors among computer workers and consequently in the secondary prevention of WUEMSDs.